Companion Proceedings of the Web Conference 2022 2022
DOI: 10.1145/3487553.3524935
|View full text |Cite
|
Sign up to set email alerts
|

Expressing Metaphorically, Writing Creatively: Metaphor Identification for Creativity Assessment in Writing

Abstract: Metaphor, which can implicitly express profound meanings and emotions, is a unique writing technique frequently used in human language. In writing, meaningful metaphorical expressions can enhance the literariness and creativity of texts. Therefore, the usage of metaphor is a significant impact factor when assessing the creativity and literariness of writing. However, little to no automatic writing assessment system considers metaphorical expressions when giving the score of creativity. For improving the accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…One major concern is the ability of AI systems to accurately assess complex or subjective aspects of writing, such as creativity, originality, or nuanced arguments. Zhang et al (2022) proposed a novel creativity assessment model based on the pre-training of deep bidirectional transformers (BERT) that imports a token-level metaphor identification method to extract metaphors as the indicators for creativity scoring. The experimental results showed that the model can accurately assess the creativity of different texts with precise metaphor identification.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One major concern is the ability of AI systems to accurately assess complex or subjective aspects of writing, such as creativity, originality, or nuanced arguments. Zhang et al (2022) proposed a novel creativity assessment model based on the pre-training of deep bidirectional transformers (BERT) that imports a token-level metaphor identification method to extract metaphors as the indicators for creativity scoring. The experimental results showed that the model can accurately assess the creativity of different texts with precise metaphor identification.…”
Section: Literature Reviewmentioning
confidence: 99%